Color priming in pop-out search depends on the relative color of the target - Becker, Stefanie I.; Valuch, Christian; Ansorge, Ulrich (Frontiers in Psychology, 2014)
In visual search for pop-out targets, search times are shorter when the target and non-target colors from the previous trial are repeated than when they change. This priming effect was originally attributed to a feature weighting mechanism that biases attention towards the target features, and away from the non-target features. However, more recent studies have shown that visual selection is strongly context-dependent: According to a relational account of feature priming, the target color is always encoded relative to the non-target color (e.g., as redder or greener). The present study provides a critical test of this hypothesis, by varying the colors of the search items such that either the relative color or the absolute color of the target always remained constant (or both). The results clearly show that color priming depends on the relative color of a target with respect to the non-targets but not on its absolute color value. Moreover, the observed priming effects did not change over the course of the experiment, suggesting that the visual system encodes colors in a relative manner from the start of the experiment. Taken together, these results strongly support a relational account of feature priming in visual search, and are inconsistent with the dominant feature-based views.